Mumbul Park and Lele Village: Tourism and Creative Economy Potential in Bojonegoro Regency - Rahmawati, Widya; Sudarwati, Emy; Wani, Yudi Arimba; Nugroho, Gabryna Auliya; Ekawaty, Marlina; Puspitasari, Diyah Ayu (Journal of Innovation and Applied Technology, 2023)
Kalianyar, Kalirejo and Pacul villages were three villages in the Bojonegoro Regency that have tourism and creative economy potential. Kalianyar Village had Mumbul Park tourist destination, while Kalirejo and Pacul Villages have the potential in the form of community fishponds which can become tourist destinations and producers of catfish. This Strategic Community Service Activity aimed to strengthen facilities and improve community skills in utilising their potential. These community service activities included: 1) Revitalization of Mumbul Park; 2) Training on making souvenirs; 3)  Improvement of fish pond and foodstalls facilities; 4) Training on catfish feed from Moringa leaves; 5) Training on making flossed catfish; 6) Improvement of catfish pond facilities and installation of biopores; 7) Catfish cultivation in buckets training; 8) Training on making catfish nuggets and chicken dimsum; 9) Socialization of food diversification and fish-eating movement; 10) Socialization of applications for halal certification.